Dentists Knowledge about Association of Systemic Health with Periodontal Disease - Hafsa Feroze, Syed Akbar Abbas Zaidi, Waheed Gul Shaik, Talha Tanveer, Misbah Ali, Mehmil Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: This study designed to evaluate the necessity for interdisciplinary dental and medical education by assessing clinicians’ awareness of the relation between systemic health and periodontal disease. Study design: A Cross-sectional and Descriptive study. Place and Duration: In the Dental department of Hamdard University Dental Hospital, Karachi for six-months duration from July 2021 to December 2021. Methods: A sample of 200 dentists and physicians was designated using convenient technique of sampling. A self- validated and pre-validated questionnaire consisting of questions about the knowledge of the relationship between systemic health and periodontal disease among dentist was used. Data was analyzed using SPSS 24.0. Results: While 184 out of 200 dentists agreed that there was a link between periodontal disease and systemic health, 16 disagreed. Most (194) participants were aware of the periodontal disease and its associated signs and symptoms, and (6) were unaware of these symptoms. While most dentists (172) considered bleeding from the gingiva to be the major symptom clinically of periodontal disease, 102 dentists reported gingival pain as the primary symptom. In addition, most dentists (185) have stated that they have awareness about the relation between periodontal disease and diabetes, while 172 dentists have stated that cardiovascular disease and obesity are associated with periodontal disease Conclusion: The information on the association between systemic health with periodontal disease among practitioners was satisfactory. Keywords: Diabetes, cardiovascular diseases, obesity, gingival bleeding, systemic health and periodontal disease